Less known facts and findings about TiO2 nanotubes - Tsuchiya, Hiroaki; Schmuki, Patrik (Nanoscale, 2020)
Anodic TiO2 nanotubes that are grown on Ti substrates by a simple anodization in various types of fluoride containing electrolytes have attracted scientific and technological interest due to their wide potential applications, and therefore, numerous research efforts have been dedicated to these self-ordered oxide structures in the past decade. The present mini-review highlights less known but important aspects, such as the formation of spaced nanotubes with adjustable interspacing that is achieved in a few specific organic electrolytes, and strong effects of the metallic Ti substrate which significantly affect the growth of the tubes. We discuss the formation of oxide nanotubes grown from adequately alloyed substrates and noble metal nanoparticle decoration of tubes. We describe how specific heat-treatment can introduce a nanotwinned boundary in the oxide tube walls of single-walled nanotubes obtained by a decoring process. All the facts and findings were studied in recent years and TiO2 nanotubes can be upgraded with more optimized functionalities for their applications.
CRIS-Team Scopus Importer:2020-05-02